An extension of Franklin's randomized response technique for multi-proportions. Issue 16 (17th August 2016) - Javed, M.; Sidhu, S. S.; Singh, Sarjinder
ABSTRACT: In this article, we introduce six estimators, three based on row averages and the remaining three on column averages of population proportions for trichotomous population when randomized response sampling with a normal randomizing distribution is used. The estimators have been obtained using the method of moments. All the proposed estimators are shown to be unbiased and their variances have been worked out. The percent relative efficiencies of the column total based estimators with respect to row total based estimators are investigated through empirical study.